2002
DOI: 10.1038/sj.ejcn.1601318
|View full text |Cite
|
Sign up to set email alerts
|

Randomised double-blind trial of the effect of vitamin A supplementation of Indonesian pregnant women on morbidity and growth of their infants during the first year of life

Abstract: OBJECTIVE:To investigate whether supplementation with vitamin A together with iron of Indonesian pregnant women decreases morbidity and improves growth of their infants during the first year of life. DESIGN: Women from a rural area in West Java, Indonesia, were randomly assigned on an individual basis to double-blind supplementation once weekly from $ 18 weeks of pregnancy until delivery. Supplementation comprised 120 mg iron and 500 mg folic acid with or without 4800 RE vitamin A. Their newborn infants were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Stein et al determined the impact of nutritional supplementation provided during the early childhood of women on the height of the subsequent generation (4) . Lind et al, Mwanri et al and Schmidt et al also reported the effects on growth of children (5,35,36) ; however, they also administered nutritional supplements to the children or pregnant women participating in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Stein et al determined the impact of nutritional supplementation provided during the early childhood of women on the height of the subsequent generation (4) . Lind et al, Mwanri et al and Schmidt et al also reported the effects on growth of children (5,35,36) ; however, they also administered nutritional supplements to the children or pregnant women participating in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal underweight is believed to increase the risk for low birth weight and intrauterine growth retardation, 1,6,[9][10][11][12][13][14] leading to undernutrition in infancy and childhood. 1,6,[9][10][11][12][13][15][16][17][18][19][20][21][22][23][24] Although nutritional stress during pregnancy may influence childhood nutritional status, many confounding factors could generate noncausal links between maternal nutritional status and offspring outcomes. One approach to strengthen causal inference in assessments of intrauterine influence is to compare the strength of associations between an exposure among mothers and offspring outcomes and the same exposure among fathers and offspring outcomes.…”
mentioning
confidence: 99%
“…We identified seven titles in Chinese [24]–[30] and thirty titles in English [11][13], [15], [16], [22], [23], [31]–[54] that were potentially eligible. Of the seven Chinese studies, five were about effects of one or two micronutrients supplementation during pregnancy on posterity growth and were excluded [25]–[29].…”
Section: Resultsmentioning
confidence: 99%
“…The average birth weight of children in the multimicronutrient supplementation group was heavier than that of the children in the iron+folic group in the trial from Iran, the difference did not persist postnatally [15]. However, Schmidt et al [16] failed to observe any differences of height gain between multimicronutrient and control groups during the first year of infancy. By contrast, children in the multimicronutrient group seemed to grow faster than their counterpart in the control group in the study by Zekavat et al, though the net height did not differ significantly [15].…”
Section: Introductionmentioning
confidence: 86%